Mercury Levels in the River Water and Urine of Traditional Gold Miners in Hulawa Village East Sumalata District North Gorontalo Regency - Hiola, Rama; Hiola, Reni (International Journal of Multidisciplinary Applied and Science Research, 2025)
Gold mining process with mercury is conducted by separating gold from the sands through amalgamation process and combustion process mostly conducted by group of traditional gold miners. This research aims to know mercury levels correlation in the river water and urine of traditional gold miners. This research used research design of Analytical Survey with Cross Sectional Study approach to be analyzed using pearson correlation test. Result. The research result showed that there were 2 rivers with mercury levels of 0.0213 ppm and 0.0183 ppm respectively in which it did not met the requirement of threshold value, while the urine sample that been tested in this research met the requirement of threshold value. Based on the result if pearson correlation analysis, it was obtained r value = 0.073, then correlation of mercury levels in the river water and urine of traditional gold miners was in very low category. Discussion. It is suggested to the gold miners in which they should not dispose mining waste to the river without waste treatment process first in order to not damage the environment around such as river ecosystem and people around